Resisting and Reconstructing the Borders of Patriarchal Culture in Pragati Rai’s Thaangraa [A Creeper's Stand] - Rai, Jiwan Kumar; Bista, Asmita (JODEM: Journal of Language and Literature, 2025)
This article analyses the Nepali novel Thaangraa written by Pragati Rai aiming to explore the conflict and sufferings that are created by the borderline of rigid patriarchal culture in general. Particularly, this study aims to interpret perpetual resistance to the normative values and standards of patriarchal culture that are deeply rooted in Nepali society for centuries. The study also explores how defiant characters deconstruct the established borderline of the patriarchal culture and reconstruct the alternative morals against the patriarchal beliefs that is only the male children (sons) can continue the clan of particular family. Textual analysis method has been used to interpret the novel. From the lens of Cultural Studies, Michel Foucault’s concept of resistance and Antonio Gramsci’s notion of counter-hegemony have been applied as theoretical tools to analyze the novel. The defiant character such as Soma resists sturdily established patriarchal values and its domination as Foucault argues, where there is power there is resistance. Moreover, she deconstructs the normative values of patriarchal culture by reconstructing alternative values as Gramsci opines counter-hegemony emerges when hegemony is in crisis. In Thaangraa, female characters, mainly Soma resists and reconstructs the borderlines of Patriarchal culture to claim identity, equality and dignity of women who have been suffering from the cultural values of patriarchy. For this, she keeps her husband in her maternal home and gives her father’s surname to her children claiming that daughters can support and continue the clan of the family. This study helps see dominant cultural values critically and gives insights to adopt alternative values and ideologies.